Possibility of use of Artificial Intelligence in the whole claim settlement process on insurance companies’ vehicle claims - Sesztakov, Viktor (Design of Machines and Structures, 2023)
The paper introduces the possibility of use of Artificial Intelligence in the whole claim settlement process on insurance companies’ vehicle claims. A fully automated vehicle claim settlement needs to develop the automatic liability check of the accident, which is now only made by human experts. The main points of this article are the main directions of the possible future development, such as to recognize the traffic situation, and to make a proper accident reconstruction.